Strategi Pemerintah Desa dalam Pemberdayaan Masyarakat melalui Program Desa Mandiri - Zuli Kasmawanto (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2025)
This research is based on the low level of community participation and independence in village development, which is a major obstacle in creating an empowered and sustainable village. This research aims to analyze the village government's strategy in empowering the community through the implementation of the Independent Village Program, with a case study in Pucangro Village. The method used in this research is descriptive qualitative with data collection techniques through observation, in-depth interviews, and documentation. The results show that the village government's strategy includes the implementation of skills training, strengthening MSMEs, developing BUMDes, and involving the community in program planning and implementation. The program provides positive impacts on the economic, social, and participatory aspects of the community. However, several obstacles are still encountered, such as limited humanresources, low participation of some residents, as well as regulatory challenges and local culture. This research recommends the need to strengthen collaboration across sectors and increase the capacity of village institutions to encourage the sustainability of empowerment programs. The findings are expected to be a reference for policy makers and future researchers in developing community-based developmentstrategies.